2020
DOI: 10.1016/j.compbiolchem.2020.107325
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening of approved drugs as potential SARS-CoV-2 main protease inhibitors

Abstract: The global emergency caused by COVID-19 makes the discovery of drugs capable of inhibiting SARS-CoV-2 a priority, to reduce the mortality and morbidity of this disease. Repurposing approved drugs can provide therapeutic alternatives that promise rapid and ample coverage because they have a documented safety record, as well as infrastructure for large-scale production. The main protease of SARS-CoV-2 (Mpro) is an excellent therapeutic target because it is critical for viral replication; however, Mpro has a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 62 publications
0
62
0
1
Order By: Relevance
“…Currently, scientific community are largely focused in the screening of – (i) FDA-approved drug databases, (ii) clinical trials molecules and/or (iii) previously reported coronavirus inhibitors 9 . In silico virtual screening (VS) techniques are proficient to explore CoV protease inhibitors 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . Yu and co-workers 40 reported the computational screening and findings with regard to potential binding luteolin and other natural compounds against Mpro.…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
“…Currently, scientific community are largely focused in the screening of – (i) FDA-approved drug databases, (ii) clinical trials molecules and/or (iii) previously reported coronavirus inhibitors 9 . In silico virtual screening (VS) techniques are proficient to explore CoV protease inhibitors 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 . Yu and co-workers 40 reported the computational screening and findings with regard to potential binding luteolin and other natural compounds against Mpro.…”
Section: Search Of Protease Inhibitors Against Covid-19mentioning
confidence: 99%
“…Another approach that has been opted for the treatment of COVID-19 is drug repurposing (Baby et al, 2020 ; Beck et al, 2020 ; Bharadwaj et al, 2020 ; Hage-Melim et al, 2020 ; Hakmi et al, 2020 ; Jimenez-Alberto et al, 2020 ; Kandeel & Al-Nazawi, 2020 ; Kumar et al, 2020 ). Drug repurposing is commonly employed to identify potential drugs against different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several drug repurposing options are being considered and are under investigation to control the COVID-19, as there is an urgent requirement for an effective drug or combination of drugs to combat this disease. Several efforts were executed to design novel inhibitors or employ drug repurposing approach to identify anti-COVID-19 drugs, which can act as promising inhibitors against coronavirus protease (Baby et al, 2020 ; Beck et al, 2020 ; Bharadwaj et al, 2020 ; Hage-Melim et al, 2020 ; Hakmi et al, 2020 ; Jimenez-Alberto et al, 2020 ; Kandeel & Al-Nazawi, 2020 ; Kumar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A global collaboration examining the SARS-CoV-2 protein interaction map, has identified 29 approved drugs that may have activity against SARS-CoV-2 (Gordon et al, 2020) opening up further treatment possibilities. M pro has been a popular inhibition target and diverse drugs have been reported to block its biological action (Jim enez-Alberto et al, 2020;Jin et al, 2020). A study by Pant et al (2020) used a DBVS approach to calculate the binding affinity of FDA approved protease inhibitors against SARS-CoV-2 M pro .…”
Section: Drug Repurposing Using In Silico Drug Designing Methods For Smentioning
confidence: 99%